Machine perfusion of circulatory determined death hearts: a scoping review - Saemann, Lars; Guo, Yuxing; Ding, Qingwei; Zhou, Pengyu; Karck, Matthias; Szabó, Gábor; Wenzel, Folker (Transplantation reviews, 2020)
Background - Ex vivo machine perfusion (EVMP) is reported to can successfully be applied for donor heart preservation. To respond to the organ shortage, some centres also accept hearts from marginal donors such as non-heart beating donors (NHBD) or hearts donated after cardiac death (DCD) for heart transplantation (HTx). Clinical as well as preclinical science on EVMP of DCD hearts seems to be promising but the ideal perfusion practice itself appears unclear. - Objectives - In accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA), this systematic review scopes all EVMP techniques for human and animal DCD heart preservation and addresses three specific questions, which refer to (a) the perfusion solutions, (b) the perfusion parameters and respective target values and (c) if possible, a direct comparison between cold static storage (CSS) and EVMP. - Results - Search results predominantly consisted of animal studies. Either perfusion with a crystalloid or blood-based solution, each with cardioplegic or non-cardioplegic properties was used. Some perfusates were supplemented with specific pharmacological medication to block pathophysiological pathways, which are involved in ischemia/reperfusion injury or edema formation. Besides normothermic EVMP with oxygenated blood, a wide range of temperature was applied in all approaches, with the lowest temperature at 4 °C. Pressure controlled anterograde Langendorff perfusion was applied mostly. If investigated, crystalloid machine perfusion was presented superior to CSS. - Conclusions - Only blood based EVMP was introduced into clinical practice. More research, clinical as well as preclinical, is needed to develop the ideal EVMP technique, in terms of blood or crystalloid perfusion.
Gesehen am 18.03.2021